Introduction of medication review and medication report in Swedish hospital and primary care, using a theory-based implementation strategy - Siw Carlfjord; Eva Malmberg; Carina Skoglund (BMC, 2020)
Abstract Background The development of routines regarding medication is important to avoid medication-related harm. Medication review and medication reports have earlier been found to be effective, but their implementation is not always successful. The aim of this study was to evaluate the introduction of medication review/medication report in hospital and primary care, in terms of perceptions of the implementation strategy, adoption and sustainability, in one Swedish county. Methods The study included 105 clinics. Data was collected from interviews with managers immediately after implementation, survey data and registry data collected five years later. Quantitative data was analysed using non-parametric statistical tests. Open-ended questions were analysed with qualitative methods. Results The implementation activities were found satisfying, and managers were satisfied with their own influence over the process. After five years medication review and medication reports were reported mainly implemented by the managers. Facilitating factors reported were routines, staff influence, dedication, reminders, and a stable workforce, while hindering factors reported were organizational factors, less commitment and flaws in reporting. Registry data showed that performance of medication review was very limited in primary care. In hospital care medication review was registered in about one fifth of the patients, while medication reports, only relevant for hospital care, was registered in half of the patients. Conclusions The managers' perceptions of the implementation process were mainly positive, and they found the new practices of medication review/medication report implemented. Implementation success, however, was not supported by registry data, showing the need for reliable outcome measures for implementation.